Upregulated LIMD1 alleviates pressure overload-induced cardiac hypertrophy via inhibits YAP1/AKT/GSK3β signaling - Fengwen Xie; Bin Yuan; Ye Zhang; Liru Chen; Yingmei Zhong; Quan Xu (PLoS ONE, 2025)
Objectives Pathological cardiac hypertrophy plays a significant role in the development and progression of heart failure (HF). LIM Domain Containing 1 (LIMD1) serves as a crucial regulatory factor in protein-protein interactions during cellular signal transduction. This study aims to investigate the specific roles and mechanisms of LIMD1 in pathological cardiac remodeling. Methods We employed an adeno-associated virus 9 (AAV9) system to overexpress LIMD1 in the hearts through tail vein injection. C57BL/6 mice underwent transverse aortic constriction (TAC) for four weeks. Cardiac function was assessed using echocardiography, while cardiac remodeling was evaluated through histopathology and molecular techniques. Results Our findings demonstrated elevated levels of LIMD1 in murine hearts subjected to TAC treatment and H9c2 cells challenged with angiotensin II (Ang II). Compared with wild-type (WT) mice, those injected with AAV-9-LIMD1 exhibited significantly reduced TAC-induced cardiac dysfunction, hypertrophy, and fibrosis. Mechanistically, both in vitro and in vivo experiments suggested that the beneficial effects of LIMD1 might be associated with the inhibition of the YAP1/AKT/GSK3β signaling pathway. Conclusion In summary, this study is the first to demonstrate the protective effects of LIMD1 against TAC-induced pathological cardiac remodeling. These effects are attributed to the inhibition of the YAP1/AKT/GSK3β signaling pathway.